2020
DOI: 10.14341/dm10154
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction, disease management attitudes and nutritional status of diabetes mellitus patients in Azad Kashmir, Pakistan: a hospital based cross-sectional study

Abstract: BACKGROUND: The life satisfaction of diabetes mellitus patients in association with the disease management attitudes and nutritional status have never been investigated yet in Pakistani administered Azad Jammu Kashmir. AIM: The purpose of this study is to analyze the patient satisfaction about life with diabetes mellitus in association with disease management and nutritional status. METHODS: A cross sectional survey was conducted among 496 patients in DHQ hospital, Mirpur Azad Jammu Kashmir. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Petterson et al [ 45 ] conducted a study that included 1000 diabetic participants and showed that patients with a longer duration of diabetes exhibited lower levels of energy, and overall well-being, as well as higher levels of depression. Among the DM patients interviewed, 64% of participants expressed dissatisfaction with their life [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Petterson et al [ 45 ] conducted a study that included 1000 diabetic participants and showed that patients with a longer duration of diabetes exhibited lower levels of energy, and overall well-being, as well as higher levels of depression. Among the DM patients interviewed, 64% of participants expressed dissatisfaction with their life [ 46 ].…”
Section: Discussionmentioning
confidence: 99%